Heat capacity of p-H2-p-D2-Ne solid solution: Effect of (p-D2)Ne clusters - Bagatskii, M.I.; Minchina, I.Ya.; Bagatskii, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The heat capacity of a solid solution of 1% p-D2 and 0.25% Ne in p-H2 has been investigated in the interval DT = 0.5–4 K. An excess heat capacity DCNe of this solution exceeding the heat capacity of the 1% p-D2 in p-H2 solution has been detected and analyzed. It is found that below 2 K the dominant contribution to the heat capacity DCNe is made by the rotation of the p-D2 molecules in the (p-D2)Ne type clusters. The number of (p-D2)Ne clusters in the solid sample is strongly dependent on the conditions of preparation. The splitting of the J = 1 level of the p-D2 molecules in the (p-D2)Ne clusters D = 3.2 K is consistent with the theoretical estimate.